The Addams Family - Tiernan, Greg; Vernon, Conrad; Lieberman, Matt, 1972-; Rivinoja, Erica; Berman, Gail, 1956-; Schwartz, Alex (Alexandra L.); Isaac, Oscar; Theron, Charlize; d; Wolfhard, Finn, 2002-; Universal Pictures Home Entertainment (Firm) (Universal City, CA : Universal Pictures Home Entertainment, 2020)
The first family of Halloween is back on the big screen in the first animated comedy about the kookiest family on the block.
Title from web page.
Originally released as a motion picture in 2019.
Wide screen (1.85:1).
Special features: Deleted and extended scenes; Charades with Thing; Life of a scenes; Welcome to the family; Addams Family throwback; "Haunted heart" lyric video; "My family" lyric video.
Keywords: Addams family (Fictitious characters) -- Drama; Eccentrics and eccentricities -- Drama; Families -- Drama; Feature films